Effect of twinning on productive and reproductive parameters in cows of Costa Rican specialized dairy herds (Ciencias Veterinarias, 2013)
The objective of this study was to determine the effect of twinning (TB) on productive and reproductive parameters on Holstein and Jersey cows in specialized dairy farms in Costa Rica fron 2000 to 2009. A descriptive retrospective longitudinal study,  was conducted of lactations recordered in VAMPP Bovino. The TB effect of  on productive and reproductive parameters was determined using a mixed linear regression model with herd-year-calving season as the random effect variable. Cows with TB presented the highest frequencies of calving interval (CI), services per conception (S/C), and calving-conception interval (CCI) rated as high (> 65 percentile) after the analyzed birth. On the other hand, as milk yield (kg/305d) decreased, the percentage of cows with TB also decreased. There was a significant effect of the TB, corrected by breed, lactation number, ecological zone in the farm, retained placenta, type of birth and kg/305d in previous lactation on the analyzed productive and reproductive parameters. Consequently, cows with TB had + 15.1 days of CCI (P < 0.0001), + 0.11 S/C (P < 0.005), and + 15.3 days of CCI (P < 0.0001). In addition, milk production was 153.3 kg higher in cows with TB (P = 0. 0007), once corrected by the variables included in the models for CI, S/C, and CCI. Effects of all these independent variables were observed in the productive and reproductive variables analyzed. In conclusion, TBs significantly affect productive and reproductive parameters regardless of breed, parity number and ecological zone, making them less efficient. Cows having high possibility of significant negative effects on their productive and reproductive performance may be identified if the combined effects, reported in this study are analyzed. Subsequent studies should aim at the economic effect of the TB in specialized dairy farms in Costa Rica.